MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MENJAHIT DENGAN BERBAGAI POLA PADA ANAK USIA 5-6 TAHUN KELOMPOK B2 TK AISYIYAH BAGAN HULU KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Nursafrida Nursafrida; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is lacking improving children's ability to fine motor, some children may not be able to use their fine motor properly, cutting can not, following the pattern of undeveloped child, in imitating the form of images provided can not, stick drawing and coloring still crossed the line, therefore, necessary efforts to improve fine motor skills of children, through sewing. the purpose of this research was to determine whether there is an increase in the fine motor skills of children through tailoring activities and to determine how the increase that occurred. This type of research is classroom action research conducted in two (2) cycles. data collection tool used in this study is in the form of observation sheet. the number of samples in this study were 16 children consisting of 7 boys and 9 girls. Based analysis of the assessment process there was an increase of 2 cycles. an increase that occurred from before the action to 33,33% cycle 1, cycle 1 to cycle 2 at 43.20%, and the increase before the cycle to cycle 2 at 90.93%. The results of these studies can be concluded that by tailoring activities can improve fine motor skills of children aged 5-6 years in kindergarten Aisyiyah Bagan Hulu district bangko rokan districts downstream.Keywords: Fine Motor, Sewing